Legacy of engagement in Southeast Asia - Murphy, Ann Marie; Welsh, Bridget 1971- (Institute of Southeast Asian Studies, 2008)
A collection of essays that explores the dramatic political, economic, and social transformations in Southeast Asia since 1945. It traces three themes - transformations within Southeast Asian countries, the actors and processes that contributed to these changes, and new dynamics in foreign relations.